Influence of low-flow time on survival after extracorporeal cardiopulmonary resuscitation (eCPR) - Wengenmayer, Tobias (Crit Care, 2017)
BACKGROUND: Venoarterial extracorporeal membrane oxygenation (VA-ECMO) support under extracorporeal cardiopulmonary resuscitation (eCPR) is the last option and may be offered to selected patients. Several factors predict outcome in these patients, including initial heart rhythm, comorbidities, and bystander cardiopulmonary resuscitation (CPR). We evaluated outcomes of all VA-ECMO patients treated within the last 5 years at our center in respect to low-flow duration during CPR. METHODS: We report retrospective registry data on all patients with eCPR treated at a university hospital between October 2010 and May 2016. RESULTS: A total of 133 patients (mean age 58.7 ± 2.6 years, Simplified Acute Physiology Score II score at admission 48.1 ± 3.4) were included in the analysis. The indication for eCPR was either in-hospital or out-of-hospital cardiac arrest without return of spontaneous circulation (n = 74 and 59, respectively). There was a significant difference in survival rates between groups (eCPR in-hospital cardiac arrest [IHCA] 18.9%, eCPR out-of-hospital cardiac arrest [OHCA] 8.5%; p < 0.042). Mean low-flow duration (i.e., duration of mechanical CPR until VA-ECMO support) was 59.6 ± 5.0 minutes in all patients and significantly shorter in IHCA patients than in OHCA patients (49.6 ± 5.9 vs. 72.2 ± 7.4 minutes, p = 0.001). Low-flow time strongly correlated with survival (p < 0.001) and was an independent predictor of mortality. CONCLUSIONS: Time to full support is an important and alterable predictor of patient survival in eCPR, suggesting that VA-ECMO therapy should be established as fast as possible in the selected patients destined for eCPR. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s13054-017-1744-8) contains supplementary material, which is available to authorized users.